2004
DOI: 10.1016/s0749-8063(04)00809-6
|View full text |Cite
|
Sign up to set email alerts
|

A new technique of graft harvest for anterior cruciate ligament reconstruction with quadruple semitendinosus tendon autograft

Abstract: A new technique of graft harvesting was used in 8 cases for arthroscopic anterior cruciate ligament reconstruction with quadruple semitendinosus tendon autograft. The graft is acquired through a small incision on the posteromedial aspect of the knee at the flexor crease instead of the standard anteromedial approach through a paramedian incision. Compared with the standard technique of graft harvesting, this new method of graft harvest facilitates easier identification of the semitendinosus and avoids inadverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Franz and Prodromos described the technique of posteromedial ST tendon harvest with the purpose of minimizing iatrogenic injury to the IBSN and SBSN 15,23 . Low complication rates have also been reported by several authors who have used the posteromedial approach 15,16,19,24,25 . Our study is in accordance with these reports.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Franz and Prodromos described the technique of posteromedial ST tendon harvest with the purpose of minimizing iatrogenic injury to the IBSN and SBSN 15,23 . Low complication rates have also been reported by several authors who have used the posteromedial approach 15,16,19,24,25 . Our study is in accordance with these reports.…”
Section: Discussionmentioning
confidence: 69%
“…To our knowledge, there are no reports in the literature about iatrogenic damage to the IBSN or SBSN during isolated posterior ST harvesting. Moreover, posterior harvesting allows for shorter operating times, easier ST tendon identification, better cosmetic results and greater patient satisfaction 15,18,24 . When retrograde tibial drilling is used, the scar over the anterior tibia is minimal and the harvesting wound scar is hidden in the popliteal fossa.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopically assisted ACL reconstruction using medial hamstring tendons is not free of complications such as disinsertion of the pes anserinus, amputation of the graft, and injury to the IPBSN. 13 Vertical, horizontal, and even oblique incision methods have been proposed for medial hamstring tendon harvesting, at an approximate distance of 2.5 to 4 cm from the tibial tuberosity.…”
Section: Discussionmentioning
confidence: 99%
“…12,28 Kodkani et al reported that two incisions, one is at 1 cm distal of tuberositas tibia, another at flexion line of the knee, are safer in hamstring tendon harvest. 31 All authors accept the knee to be kept in flexion and thigh is recommended to be kept in external rotation during graft harvest. So, saphenous nerve goes to posterior and draws away from the surgical site.…”
Section: Discussionmentioning
confidence: 99%